Honey, I shrunk the genre. - Miao, Kathi (Fantasy & Science Fiction)
Presents the author's reasons why she has trouble accepting movies based on comic book characters as science fiction films. Decline in the thematic spectrum of so-called science fiction movies; Criticism of the movie `Barb Wire'; Movie `The Mask' as amusing and fun to watch; Recommendation of the animated movie `James and the Giant Peach.'